Postinterview Communications: Two Surveys of Internal Medicine Residency Program Directors Before and After Guideline Implementation. (September 2018) - Chacko, Karen M.; Reddy, Shalini; Kisielewski, Michael; Call, Stephanie; Willett, Lisa L.; Chaudhry, Saima
Abstract : Purpose: Guidelines surrounding postinterview communication (PIC) after residency interviews were issued by the National Resident Matching Program and Association of Program Directors in Internal Medicine. How they have influenced PIC and program directors' (PDs') reasons for PIC is unknown. Method: Annual surveys of 365 U.S. internal medicine residency PDs in 2013 and 368 in 2015 were used. Questions about frequency, intent, and usefulness of PIC and knowledge of guidelines before and after new PIC guidelines were included. Chi-square tests were used to compare data sets, and multivariate logistic regression was performed for 2015 data to identify factors predicting engagement in PIC, using program characteristics, PD characteristics, and beliefs about the benefits of PIC as independent variables. Results: There were 265 (73%) respondents in 2013 and 227 (62%) in 2015. While the number of programs with a PIC policy increased 43%, the level of contact increased 7%. Few PDs indicated PIC was helpful to them; however, PDs who felt PIC helps target applicants were more likely to engage in PIC (OR 4.21, SE 1.88, P = .001). The main reason for continuing PIC (50% of PDs) was that PIC, part of their program's culture, was considered "good manners." Conclusions: New guidelines increased the number of programs with a PIC policy, but the overall rate of applicant contact did not change despite few PDs feeling PIC was helpful to recruitment. The culture surrounding PIC may be difficult to overcome via guidelines alone, and more definitive rules are necessary to implement change. Abstract : Supplemental Digital Content is available in the text.